The effects of spatial and contextual factors on headquarters resource allocation to MNE subsidiaries - Dellestrand, Henrik; Kappen, Philip (Journal of International Business Studies, 2012)
Subsidiaries of multinational enterprises are located in a range of environments, in which they are exposed to organizational, national, and sub-national characteristics. Instead of being distributed equally, economic resources are agglomerated in specific countries, or even regions, and the subsidiaries located in these different environments have a heterogeneous resource configuration. This implies that dimensions of space related to geography and subsidiary network relationships may affect how the firm is managed. This paper investigates how spatial and contextual distance within multinational enterprises affects headquarters resource allocation to specific innovation transfer projects between subsidiaries. In brief, the results suggest that sub-national factors, such as the structure of the subsidiary network, offer a strong explanation for headquarters resource allocation. Positive and negative effects of national factors were also found, which implies that distance matters for headquarters resource allocation activities. By integrating the organizational and geographic dimensions, this paper contributes to knowledge about the drivers of headquarters resource allocation to subsidiaries, thereby extending theories related to how subsidiaries can evolve within the multinational enterprise with support from headquarters.